2021
DOI: 10.1039/d1cp03142b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of melatonin binding and destabilizing the protofilament and filament of tau R3–R4 domains revealed by molecular dynamics simulation

Abstract: Microsecond all-atom molecular dynamics simulations reveal that melatonin can destabilize the protofilament and filament of tau R3–R4 domains. Its influence on tau structure, binding kinetics and sites, and the disruptive mechanism are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…Mel preferentially binds to aromatic F23, followed by hydrophobic I26 and L27, while it has a similar binding affinity to the rest of the residues. Our previous study showed that the binding of Mel to a tau protein is dominated by H-bonding between Mel and the peptide backbone and is synergistically aided by other interactions [ 48 ]. Here, the binding of Mel to the hIAPP 20–29 octamer exhibits a similar behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Mel preferentially binds to aromatic F23, followed by hydrophobic I26 and L27, while it has a similar binding affinity to the rest of the residues. Our previous study showed that the binding of Mel to a tau protein is dominated by H-bonding between Mel and the peptide backbone and is synergistically aided by other interactions [ 48 ]. Here, the binding of Mel to the hIAPP 20–29 octamer exhibits a similar behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular-simulation methods have long been used to study peptide aggregation, including both all-atom [ 16 , 17 , 18 ] and coarse-grained (CG) methodologies [ 19 ]. Of those, the methods based on CG models offer much longer time- and size-scales, including the possibility of simulating aggregation from scratch, even though this extension is achieved at the inevitable expense of modeling accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Although compounds with a high aromaticity value may have the ability to inhibit the aggregation of amyloid peptides, 6,[38][39][40] and many of them have relatively low inhibition potency. For example, we recently found that FeTPPS and FeTBAP have a better inhibitory effect on human islet amyloid polypeptide (hIAPP) fibril formation, 25,26 whereas, FeTMPyP, a structural analogue of FeTPPS and FeTBAP, is less effective, 26 indicating that the inhibitory effect of these ironporphyrins on hIAPP aggregation has a structure-activity relationship.…”
Section: Metalloporphyrins Inhibit Aβ 1-42 Fibrillationmentioning
confidence: 99%
“…Understanding the binding mode will help develop novel agents with anti-amyloid properties. 39,40 Therefore, answering the above questions will give a comprehensive knowledge to the selectivity of metalloporphyrins in stabilizing Aβ 1-42 monomers and the final different inhibitory effects on the aggregation of Aβ 1-42 .…”
Section: Metalloporphyrins Selectively Stabilize Aβ 1-42 Monomersmentioning
confidence: 99%